If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -7x = 3 + -8x Solving 11 + -7x = 3 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 11 + -7x + 8x = 3 + -8x + 8x Combine like terms: -7x + 8x = 1x 11 + 1x = 3 + -8x + 8x Combine like terms: -8x + 8x = 0 11 + 1x = 3 + 0 11 + 1x = 3 Add '-11' to each side of the equation. 11 + -11 + 1x = 3 + -11 Combine like terms: 11 + -11 = 0 0 + 1x = 3 + -11 1x = 3 + -11 Combine like terms: 3 + -11 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| 7(8+3h)= | | 42/5+42/6 | | y=3+-4x | | x/3+x/2=8/3 | | -x^2+10x+128=0 | | 11x-45=4x+39 | | 2y=24x+2 | | -4(2y-8)-y=-3(y-3) | | 5/6z=5/8 | | x^2-4x+64=0 | | (-a-7b+3)6ab= | | 25x+-6x+120=21x | | ax-7b=4c | | 2x-5(4x+10)=58 | | (3x-4)(3x-4)+16=0 | | (x-8)(x-8)-81=0 | | y/5+y/4=7/5 | | -4(6y-5)-y=-3(y-2) | | 4k^2+12K-9=0 | | 1/5x+1/4=-2 | | 5/12X=3 | | 3/8X=24 | | 1/2X=11 | | 36r*5= | | -2y-7(6y-8)=1+9(1-y) | | E=LR+Lr | | 4/9X=20/18 | | r+6=3(r-3) | | x^3=29 | | 4/9X=10/18 | | 6r*5= | | 2r+6=3(3-r) |